ISLAMIC RELIGIOUS LEARNING MANAGEMENT IN REALIZING STUDENTS’ RELIGIOUS CULTURE (MIN 1 PALI CASE STUDY) - Nikentari Rizki; Nur Aini; Saipul Annur; Nurul Arifin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Learning Islamic religious education requires good educational management in the process. Madrasas as schools have religious characteristics as seen from the learning that carries out the process of moral and mental development which is also supported by the process of cultivating a religious atmosphere in madrasa institutions. Religious culture at school also needs to be supported by the religious culture of the family at home. The existence of religious culture at home is a synchronization of religious culture at school. Which means that instilling religious values in students needs to be supported by the family environment. An example is instilling awareness of the five daily prayers which are carried out by habit at home. Therefore, the role of the family is very important in realizing the religious culture of students at school. This article uses a qualitative descriptive method to describe the religious culture at MIN 1 Pali. The techniques used by researchers to collect data in this research are as follows: in-depth interviews, participant observation, and documentation. This article uses Miles Huberman's flow analysis model, that activities in descriptive data analysis take place in three ways, namely: (1) data reduction, (2) data presentation and (3) conclusion drawing or verification.